The Map as a Tool for Explanations in Geography - Kufogbe, S.K.; Owusu, A.B.; Yiran, G.A.B. (My University, 2013)
The map as a symbolic representation on earth forms and features constitutes a very vital medium for understanding geographic reality. Explanation using the map is concerned with understanding interrelationships among location, character, and arrangement of natural and cultural features and their interactions on the surface of the earth over time. Different types of thematic maps are used by geographers alongside diagrams, tables and written accounts. The map can yield significant amount of information in the hands of the skilled user. It is for this reason that it has been described as the geographer’s most useful resource. Maps are increasingly becoming readily available through the internet. It is the belief of the authors’ that this chapter will stimulate the interest of the reader to take a second look at maps and seek to understand the messages encoded in them. Despite the power of maps as explanatory tools, very few scholars outside of geography use maps and some people are intimidated by maps. As is evident in the illustrative examples provided, professionals outside geography can also use maps no longer as decorative pieces, but more usefully in interpreting and understanding earth reality.